Techno-economic assessment of jet fuel production using the Fischer-Tropsch process from steel mill gas - Collis, Jason; Duch, Karsten; Schomäcker, Reinhard (Frontiers in Energy Research, 2022)
In order to reduce human-made global warming, the aviation industry is under pressure to reduce greenhouse gas (GHG) emissions. Production of sustainable aviation fuel (SAF) from steel mill gases could help reduce the emissions intensity of jet fuel. This study presents a simulation, techno-economic assessment, and GHG emissions assessment of a Fischer-Tropsch (FT) process using two steel mill gases (coke oven gas and blast furnace gas) as feedstock. The process was analysed both with and without carbon capture and storage (CCS) to reduce process emissions. The minimum viable sales price (MVSP) was determined to be 1,046 €/tonne for the standard scenario and 1,150 €/tonne for the CCS scenario, which is higher than the fossil-fuel-based benchmark (325 – 1,087 €/tonne since 2020), although similar to the lowest costs found for other SAF benchmarks. The GHG emissions intensity was found to be 49 gCO2-eq./MJ for the standard scenario and 21 gCO2-eq./MJ with CCS, far lower than the 88 gCO2-eq./MJ average for the conventional benchmark and in the mid-lower range of found emissions intensities for other SAF benchmarks. When a CO2 tax of 130 €/tonne is considered, the MVSP for the standard scenario increases to 1,320 €/tonne while the CCS scenario increases to 1,269 €/tonne, making them cost-competitive with the fossil-fuel benchmark (797 – 1,604 €/tonne). The studied process offers economically viable small-to-medium scale SAF plants (up to 50 kt/y SAF) at a CO2 tax of 190 €/tonne or higher for the CCS scenario and 290 €/tonne or higher for the standard scenario.